2019
DOI: 10.1002/mde.3051
|View full text |Cite
|
Sign up to set email alerts
|

Managerial overconfidence, overinvestment, and R&D spillover

Abstract: This paper examines whether a firm will select an overoptimistic manager when a cost-reduction investment has a spillover effect. We consider a Cournot competition model where R&D investment ex ante occurs before the process of product market competition. Our analysis reveals that there exists a unique and symmetric equilibrium for firms to delegate overoptimistic managers. We show that only when the spillover effect is sufficiently high do firms benefit from delegation. Furthermore, the equilibrium confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…Motivations towards overinvestment originate from the misalignment of interests between managers and investors (Shi and Gao, 2018). Managers attempt to enlarge assets under their management to accumulate personal benefits, while investors pay attention to profit maximization to raise firm value in the future (Badavar Nahandi and Taghizadeh Khanqah, 2018; Li et al , 2019). As a result, managers expand investment level, increasing the probability of investing in projects with negative net present value (NPV) (Ding et al , 2019; Bhuiyan and Hooks, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Motivations towards overinvestment originate from the misalignment of interests between managers and investors (Shi and Gao, 2018). Managers attempt to enlarge assets under their management to accumulate personal benefits, while investors pay attention to profit maximization to raise firm value in the future (Badavar Nahandi and Taghizadeh Khanqah, 2018; Li et al , 2019). As a result, managers expand investment level, increasing the probability of investing in projects with negative net present value (NPV) (Ding et al , 2019; Bhuiyan and Hooks, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate the definition of overconfidence, assume that the inverse market demand curve for a firm's product i is pi=aqibqj, where p i is product i 's price, a is the intercept or the true (or accurate) market size, q i is product i 's quantity, q j is the quantity produced by a rival company, and b is the degree of product differentiation or substitutability between the two products. Following the recent works of Englmaier (2010), Englmaier and Reisinger (2014), Yu (2014), and Li et al (2019) on managerial overconfidence, an overconfident manager of type α overestimates the market size and believes that α > a , and an unbiased manager is realistic or rational and believes that α=a. Therefore, in our specification, α ∈ [ a , ∞ ), and the level of overconfidence increases with α .…”
Section: Introductionmentioning
confidence: 90%
“…Our findings contribute to the literature that analyzes the welfare effects of managerial overconfidence in oligopolies. Inspired by previous studies, one could argue that if hiring an overconfident manager is optimal for a firm competing in output or price and the prices decrease, that welfare would improve (see, for example, Englmaier, 2010, 2011; Englmaier & Reisinger, 2014; Li et al 2019). Our analysis shows that this statement does not hold when R&D productivity is high.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when the financing ability of the company is high, overconfidence compounds overinvestment. Li et al [40] analyzed the effects that investment spillover has on a company's investment level and selection of CEOs. The authors found a symmetric equilibrium for firms to appoint overconfident managers, which only benefits firms when the spillover effect is high.…”
Section: Prior Research On Investment Efficiencymentioning
confidence: 99%